THE RELATIONSHIP BETWEEN STUDENTS' PERSONALITY MATURITY AND ETHICAL AWARENESS IN THE USE OF ARTIFICIAL INTELLIGENCE (AI) A STUDY AT LP3I JAKARTA POLYTECHNIC (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
The rapid integration of Artificial Intelligence (AI) into higher education has introduced new challenges concerning academic integrity. Although AI can effectively support students throughout the learning process, it’s inappropriate or unethical use may lead to adverse consequences for students' academic development. This study aims to examine the relationship between students' personality maturity, with particular emphasis on the dimensions of responsibility and honesty, and their AI ethical awareness, defined as the ethical consciousness surrounding the use of AI technologies. The study employed a quantitative causal research design, with data collected from a sample of LP3I Polytechnic students through a structured questionnaire. The theoretical and empirical findings indicate that personality maturity is positively and significantly associated with AI ethical awareness. Specifically, the honesty dimension plays a crucial role in mitigating AI-assisted plagiarism, while the responsibility dimension promotes the accountable and ethical use of AI technologies. The findings highlight the importance of strengthening character education and digital ethics in higher education institutions to address the challenges posed by ongoing digital technological disruption.